EKSISTENSI SARABBA SEBAGAI MINUMAN TRADISIONAL KHAS BUGIS-MAKASSAR DI ERA MODERN - Masyudi, Ayudia Rostiara; Nabila, Fadia Marsya; Abdullah, Mirna Nur Alia (Universitas Hamzanwadi, 2022)
Sarabba is a traditional drink made from ginger and brown sugar originating from South Sulawesi, especially the Bugis and Madurese tribes. The purpose of this article is to find out the potential of sarabba to become a trend like coffee among young people and what innovations have been made as an effort to maintain the existence of sarabba in this modern era. The research method used is a qualitative method using an ethnographic approach and with data collection techniques through literature studies and also interviews to related parties whose results will be in the form of words. From the results of the research, sarabba has undergone many developments starting from packaging that is starting to be attractive and varied flavors such as mocca and chocolate flavors, and currently there are many instant or powder sarabba and also the ice cream version of sarabba, so the possibility of sarabba becoming a trend like coffee among teenagers is getting bigger, considering that in Makassar itself sarabba is much loved and is everywhere. So it can be concluded that: 1) There have been many innovations to maintain the existence of sarabba in this modern era, for example the sarabba innovation carried out by Sarabba Sukma Jahe Makassar and Sarabba Indonesia stores. This innovation is done by changing the shape and creating new flavor variants. Innovation in terms of form, namely there is sarabba in instant form and sarabba in the form of ice cream. While from the flavor variants there are mocca, chocolate and milk flavors. 2) Sarabba has the potential to become a trend among young people but is still within a limited scope, namely in Makassar. With the many innovations in sarabba today, it is certainly a driving factor for sarabba to become a trend among young people. However, when compared to the coffee trend, the sarabba trend is quite difficult to realize.